Kurdish Pregnant Women's Emotions and their Effect on Choice of Delivery Method in Sanandaj, Iran - Shahoei, Roonak (2010)
A qualitative study using the grounded theory approach (Strauss and Corbin, 1998) was conducted with the purpose of discovering the emotions of Kurdish pregnant women during the first, second and third trimesters, their contributory factors, and, how their emotions affect their choice of delivery methods. Twenty-two women in their third trimesters were interviewed either at the health center or in their homes in Sanandaj, Iran. Each interview was tape recorded, transcribed verbatim and analyzed according to the constant comparative method through open, axial, and selective coding. Trustworthiness was established through member checks, peers examination, and an audit trail of the research activities. Three categories, twelve subcategories, and five sub-sub categories emerged from the data in relation to women’s emotion during pregnancy. The findings showed that the women’s emotions could be classified under four integrated domains – physical, psychological, interaction with husbands and relatives, and, interaction with baby. Apart from the physiological changes which caused the women to be uncertain about their pregnancy, their body image, financial situation and their feelings which were stimulated by the attitude of their spouses and relatives during their pregnancy affected them as well. During the third trimester, all attention was focused on the baby’s health, thus making them think more about the methods of delivery. Eighteen of the pregnant Kurdish women studied expressed preference for vaginal delivery. They said that they chose to have a natural childbirth because the baby would be safe. Based on the information mentioned above, the study put forward a substantive theory, named, ‘‘safe passage’’. This theory explains the pregnant women’s worry and consciousness to end a journey whereby healthy delivery and a healthy baby would result. The other most important finding that emerged from the data was the closer relationship between the women and their spouses. The extent of physical and emotional support they received from their husbands contributed to the healthy positional adjustment throughout their pregnancy period. Feelings of self-confidence, pleasure and satisfaction were accompanied with increase of fondness toward their babies. There was also the factor of social support from their family members. All of which contributed toward their decision for vaginal childbirth. The four women who preferred cesarean section were nuliparous. Their reasons were fear of vaginal childbirth, safety of baby and mother, and friends’ encouragement. Their fear was mainly caused by the negative experience of relatives and friends who had difficulty with natural delivery and also by the lack of information. Through this qualitative study, an insight into Kurdish pregnant women’s emotions was gained. Some practical and theoretical implications are given. Further studies are recommended.